Superfícies Invariantes no Espaço Homogêneo Sol com Curvatura Constante. - Neto., Guilherme Luiz de Oliveira (2012)
In this paper we studied surfaces with constant mean curvature and surfaces with constant Gaussian curvature in the Sol space which are invariant under the action of two one-parameter subgroups of isometries of the ambient space. Furthermore, we classify the surfaces that satisfy a relationship of type k1 = mk2, where k1 and k2 are the principal curvatures of the surface and m ∈ R.